2011
DOI: 10.1080/10572317.2011.10762883
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the information seeking behavior of Greek graduate students: A case study set in the University of Macedonia

Abstract: This paper describes a survey designed to determine the information seeking behavior of graduate students at the University of Macedonia (UoM). The survey is a continuation of a previous one undertaken in the Faculties of Philosophy and Engineering at the Aristotle University of Thessaloniki (AUTh). This paper primarily presents results from the UoM survey, but also makes comparisons with the findings from the earlier survey at AUTh. The 254 UoM students responding tend to use the simplest information search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…College students were also likely to initially use Google for their search tasks due to accessibility, familiarity, and acceptance of natural language (Currie et al, 2010;Head and Eisenberg, 2010). As undergraduates are used to convenient and easy-to-access sources, they would rather avoid resources that require complex steps to access information when performing searches (Malliari et al, 2011). Denison and Montgomery (2012) found that college students perceived online databases to be complex and inefficient, but not intuitive or less user friendly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…College students were also likely to initially use Google for their search tasks due to accessibility, familiarity, and acceptance of natural language (Currie et al, 2010;Head and Eisenberg, 2010). As undergraduates are used to convenient and easy-to-access sources, they would rather avoid resources that require complex steps to access information when performing searches (Malliari et al, 2011). Denison and Montgomery (2012) found that college students perceived online databases to be complex and inefficient, but not intuitive or less user friendly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Information retrieval behavior" is the last defined term in our review. The term refers to the search techniques and modifications of search results done by the users to receive the most suitable information sources for their need (Malliari, Korobili, & Zapounidou, 2011).…”
Section: Information Behaviormentioning
confidence: 99%
“…In developed countries, ICT-experienced students make use of ICT for learning more often than ICT-less-inexperienced students (Mark & Shearer, 2016). Teachers and students will, therefore, need digital experience if they must succeed in a technologically developing world (Malliari et al, 2011). In a study by Luu and Freeman (2011), the researchers found no significant difference in ICT proficiency level between ICT-experienced and ICT-less-experienced students.…”
Section: Introductionmentioning
confidence: 98%
“…Ofoegbu and Uche (2013) revealed that a positive perception towards ICT is widely recognized as a necessary condition for the effective use of information technology for learning. Malliari, Korobili and Zapounidou (2011) reported that undergraduates' negative perception served as a barrier towards information technology utilization for learning. Selwyn (2008) believed that undergraduates' use of ICT is influenced by several factors and these factors could be unpredictable.…”
Section: Introductionmentioning
confidence: 99%